2019
DOI: 10.3390/molecules24101894
|View full text |Cite
|
Sign up to set email alerts
|

Clitoria ternatea Flower Petal Extract Inhibits Adipogenesis and Lipid Accumulation in 3T3-L1 Preadipocytes by Downregulating Adipogenic Gene Expression

Abstract: Clitoria ternatea (commonly known as blue pea) flower petal extract (CTE) is used as a natural colorant in a variety of foods and beverages. The objective of study was to determine the inhibitory effect of CTE on adipogenesis in 3T3-L1 preadipocytes. The phytochemical profiles of CTE were analyzed by liquid chromatography and tandem mass spectrometry (LC-MS/MS). Anti-adipogenesis effect of CTE was measured by using Oil Red O staining, intracellular triglyceride assay, quantitative real-time PCR and western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
31
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 50 publications
9
31
0
6
Order By: Relevance
“…Additionally, IAE inhibited the expression of C/EBP-β and the activation of STAT3. Consistent with preceding results, previous studies have reported that plant extracts and their phytochemicals inhibit adipogenesis and lipid accumulation through suppression of MCE, which was dependent on the regulation of cell cycle progression and/or suppression of transcription factors [ 50 , 51 , 52 ]. For instance, Gleditsia sinensis fruit extract suppressed MCE and adipogenesis through the inhibition of p27 KIP1 degradation and the activation of STAT3 [ 7 ].…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, IAE inhibited the expression of C/EBP-β and the activation of STAT3. Consistent with preceding results, previous studies have reported that plant extracts and their phytochemicals inhibit adipogenesis and lipid accumulation through suppression of MCE, which was dependent on the regulation of cell cycle progression and/or suppression of transcription factors [ 50 , 51 , 52 ]. For instance, Gleditsia sinensis fruit extract suppressed MCE and adipogenesis through the inhibition of p27 KIP1 degradation and the activation of STAT3 [ 7 ].…”
Section: Discussionsupporting
confidence: 90%
“…Obesity is a state in which body fat is excessively accumulated and may cause social problems because of decreased quality of life and the development of chronic diseases. Many researchers have attempted to determine whether natural food materials are effective in preventing obesity by inhibiting adipogenesis [21][22][23][24]. Recent studies demonstrated the anti-obesity effects of extracts of Chrysanthemum indium and Chrysanthemum zawadskii in the Compositae family [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Growth of triglycerides (TG) in mature adipocyte is triggered when adipogenic transcriptional factors such as PPARγ/CCAT/enhancer-binding protein (C/EBP) are expressed [24]. It leads to a pathway to regulate fatty acid synthase (FAS) and acetyl-CoA carboxylase (ACC) [25]. PPARγ can detect lipase activity [26].…”
Section: Introductionmentioning
confidence: 99%